2021
DOI: 10.1016/j.jenvp.2021.101586
|View full text |Cite
|
Sign up to set email alerts
|

Keep Degrowth or go Rebirth? Regulatory focus theory and the support for a sustainable downscaling of production and consumption

Abstract: is an alternative sustainable social-economic model.• Using the Regulatory Focus Theory, we tested how to impact support for this model.• Labelling degrowth as Rebirth (vs. Degrowth) did not reliably change its support.• Defining degrowth in terms of Promotion (vs. Prevention) increased its support.• This research introduces the concept of degrowth to environmental psychology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 111 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…Some studies suggested that prevention-focused appeals encourage green consumption more than promotion-focused appeals [48]. Some studies have indicated that promotionfocused appeals are more effective for sustainable and reduced consumption as compared to prevention-focused appeals [69]. Zou and Chan [70] indicated both prevention-focused and promotion-focused people can engage in green behaviors with a mediating influence of ethical judgement and ethical intention.…”
Section: Covid-19-stress and Intentions For Sustainable Apparel Consu...mentioning
confidence: 99%
“…Some studies suggested that prevention-focused appeals encourage green consumption more than promotion-focused appeals [48]. Some studies have indicated that promotionfocused appeals are more effective for sustainable and reduced consumption as compared to prevention-focused appeals [69]. Zou and Chan [70] indicated both prevention-focused and promotion-focused people can engage in green behaviors with a mediating influence of ethical judgement and ethical intention.…”
Section: Covid-19-stress and Intentions For Sustainable Apparel Consu...mentioning
confidence: 99%
“…However, much less work has attempted to understand how the general public might engage with this transformative process. Psychological research has elicited perceptions of the name 'degrowth' (Drews & Reese, 2018;Krpan & Basso, 2021), appropriate frames and avenues for communicating post growth ideas to the public (O'Dell et al, 2023;Tomaselli et al, 2021), attitudes toward the growth-vs-environment debate (Drews et al, 2019;Drews & van den Bergh, 2016) and impediments to studying such attitudes . We encourage more environmental psychologists to design research agendas addressing such perception gaps, in particular by exploring differences in class, race, and perceived status, as these perspectives are currently lacking in degrowth research (Schmelzer et al, 2022).…”
Section: Liaising With Other Disciplines To Promote Transformative Ch...mentioning
confidence: 99%